IP1867B suppresses the insulin-like growth factor 1 receptor (IGF1R) ablating epidermal growth factor receptor inhibitor resistance in adult high grade gliomas. (28th August 2019) - Mihajluk, K.; Simms, C.; Reay, M.; Madureira, P.A.; Howarth, A.; Murray, P.; Nasser, S.; Duckworth, C.A.; Pritchard, D.M.; Pilkington, G.J.; Hill, R.
Abstract: High grade gliomas (HGGs) are aggressive primary brain tumours with local invasive growth and poor clinical prognosis. Clinical outcome is compounded by resistance to standard and novel therapeutics. We have evaluated reformulated aspirin (IP1867B) alone and in combination with conventional and novel anti-aHGG agents. We show that recent biopsy-derived aHGG models were highly resistant to conventional therapeutics although show sensitivity to IP1867B, a reformulated "liquid" aspirin. IP1867B treatment mediated a potent suppression of the IL6/STAT3 and NF-κB pathways and observed a significant reduction in EGFR transcription and protein expression. We observed the loss of the insulin-like growth factor 1 and insulin-like growth factor 1 receptor expression at both the transcript and protein level post IP1867B treatment. This increased sensitivity to EGFR inhibitors. In vivo, IP1867B was very well tolerated, had little-to-no gastric lesions versus aspirin and, directed a significant reduction of tumour burden with suppression of EGFR, IGF1 and IGFR1. With EGFR inhibitors, we noted a potent synergistic response in aHGG cells. These data provide a rationale for further investigation of IP1867B with a number of anti-EGFR agents currently being evaluated in the clinic. Highlights: IP1867B (liquid aspirin) significantly reduced adult and paediatric high grade glioma cell viability. IP1867B potently supressed IL6/STAT3 and NF-κB networks. IP1867B significantly reduced IGFR1 and EGFR expression and conferred sensitivity to EGFR inhibitors. IP1867B in vivo administration induced significantly less gastrointestinal lesions compared to conventional aspirin. IP1867B intraperitoneal administration induced a significant anti-aHGG response in established intracranial tumours.